Double-Row Repair for Recalcitrant Medial Epicondylitis. Issue 12 (20th December 2019) - Wu, Victor J.; Thon, Stephen; Finley, Zachary; Bohlen, Hunter; Schwartz, Zachary; O'Brien, Michael J.; Savoie, Felix H.
Background: Various techniques have been described for surgical treatment of recalcitrant medial epicondylitis (ME). No single technique has yet to be proven the most effective. Purpose: To evaluate the clinical outcomes of a double-row repair for ME. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review was performed on 31 consecutive patients (33 elbows) treated surgically for ME with a minimum clinical follow-up of 2 years. All patients were initially managed nonoperatively with anti-inflammatories, steroid injections, topical creams, and physical therapy. Outcome measures at final follow-up included visual analog scale (VAS) scores (scale, 0-10), time to completely pain-free state, time to full range of motion (FROM), Mayo Elbow Performance Scores (MEPS), and Oxford Elbow Scores (OES). Patients were contacted by telephone to determine current functional outcomes, pain, activity, functional limitations, and MEPS/OES. Successful and unsuccessful outcomes were determined by the Nirschl grading system. Results: The mean clinical and telephone follow-up periods were 2.3 and 3.6 years, respectively, and 31 of 33 (94%) elbows were found to have a successful outcome. The mean VAS improvement was 4.9 points, from 5.8 preoperatively to 0.9 postoperatively ( P < .001). The mean MEPS and OES at final follow-up were 95.1 and 45.3, respectively. The mean time to pain-free state and time to FROM were 87.4 and 96 days, respectively. Unlike prior studies, no difference in outcome was found between those with and without ulnar neuritis preoperatively ( P = .67). Conclusion: A double-row repair is effective in decreasing pain and improving the overall function for recalcitrant ME. Uniquely, the presence of preoperative ulnar neuritis was associated with higher patient-reported preoperative pain scores but not with poor outcomes using this protocol.